Teacher Strategies In Overcoming Cheating Behavior Of Elementary School Studentstitle - Zulvia Misykah; Fira Yunia; Fajar Oktaria Widarta (Outline Publisher, 2023)
Education is a bridge to educate the generation or the nation's children. The world of education has a very important role in the progress of this country. Through this world of education, the young generation or the nation's children are able to master knowledge from several domains, namely the cognitive, affective and psychomotor domains which contain moral education. However, the development of moral education for the current generation of the nation in the era of globalization is quite concerning, such as the act of cheating carried out by elementary school students today. Cheating is one of the dishonest behaviors that often occurs in the school environment, especially at the Elementary School (SD) level. This behavior not only disrupts the learning process, but also has the potential to damage the moral integrity of students from an early age. Therefore, teachers have an important role in overcoming and preventing cheating behavior among students. The problem of cheating is a serious problem because it will continue to be carried over into the world of work so that Self-Efficacy is needed, namely self-confidence in the learning process in the classroom.